The Effect of Aerobic Exercises on Blood Glucose Concentration in Healthy Girls and Girls with Type 1 Diabetes Mellitus - Sandrija Sideravičiūtė; Alina Gailiūnienė; Kristina Visagurskienė; Daiva Vizbaraitė (Lithuanian Sports University, 2018)
Regular aerobic exercises are beneﬁ cial not only for healthy people. Physical activity plays a big part in the lives of children and adolescents with type 1 diabetes mellitus too. Walking, biking, swimming, dancing, and many other activities are considered to be aerobic exercises and they are all healthy. What kind of physical exercises are the most useful for the youth with type 1 diabetes mellitus? So, the aim of the present study was to estimate and compare the effect of aerobic exercise such as swimming and aerobics, on blood glucose concentration of young girls. 19 girls aged 16.5 ± 0.24 years with the duration of diabetes for 8.1 ± 0.9 years and 28 healthy girls aged 16.9 ± 0.36 years participated in the study. Two experiments were carried out. The ﬁ rst experiment was a 7-day physical exercise program, consisting of aerobics and swimming training sessions each day. The other experiment was a 14-week swimming program, where all the participants attended swimming training sessions two times per week, and there were all in all 28 training sessions. Glycemia control was assessed by blood glucose level (mmol / l) monitored before and after every training sessions during the 7-day and 14-week physical programs. After the analysis of blood test it was found, that the 7-day physical program decreased blood glucose concentration for all subjects (p < 0.05) but, swimming had a greater effect on blood glucose control for girls with type 1 diabetes mellitus than aerobics (p < 0.01). After the 14-week duration swimming program, hyperglycemia signiﬁ cantly decre- ased for all subjects too, but it's response to the regular physical activity in the water was the highest for diabetics (p < 0.001). The evidence obtained in this study showed that both swimming and aerobics decreased blood glucose concentration for healthy subject and for subjects with diabetes. But swimming had a greater effect on the dynamics of blood glucose level for girls with type 1 diabetes mellitus than aerobics. Keywords: type 1 diabetes mellitus, swimming, aerobics, blood glucose, glycemia.